Investigating Students’ Speaking Ability at Modern Boarding School - Setiawan, Ade krisna dwi; Musarokah, Siti; Affini, Laily Nur (Journal of English Language and Education, 2024)
This research uses an explanatory mix method design. The researcher analyses and describes the students’ speaking ability through conversation tests while speaking problems experienced by students through interviews. The research finds that the eleventh-grade students of Al Falah Modern Islamic Boarding School are good at speaking. It was supported by the result of analysis. The analysis shows that 16 students have a high level of proficiency in spoken English, 10 students have a good level of speaking, 1 student has a fair level, and no students were deemed to have poor level of spoken English. At the same time, the difficulties experienced by students, including fear of making mistakes, limited vocabulary, the use of their native languages, shyness and lack of confidence were analysed through interviews. This research will serve as a valuable reference for teachers who were interested in improving their students’ communication skill.